2017
DOI: 10.1007/s11356-017-8564-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior and mechanism of ibuprofen onto BiOCl microspheres with exposed {001} facets

Abstract: BiOCl microspheres with exposed {001} facets have been synthesized through a simple solvothermal method. The adsorption and photocatalytic activities of BiOCl microspheres were evaluated by removal of ibuprofen (IBP) as the model reaction. Parameters including IBP concentration, BiOCl dosage, and inorganic ions were investigated to reveal the role of adsorption in BiOCl-based photocatalysis. We found that the high IBP removal rate by BiOCl is not due to photocatalytic oxidation but to surface adsorption. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As shown in Fig. 6(b), the band gap energy was 3.25, 2.20, and 2.39 eV for BiOCl, Bi12O17Cl2, and the composite respectively, which was similar to previous reports [47,48]. These results indicate that the Bi-OCl-Bi12O17Cl2 composite had a matching energy band position, which was conducive to photocatalytic degradation of organic pollutants under visible-light illumination.…”
Section: Uv-vis Analysissupporting
confidence: 87%
“…As shown in Fig. 6(b), the band gap energy was 3.25, 2.20, and 2.39 eV for BiOCl, Bi12O17Cl2, and the composite respectively, which was similar to previous reports [47,48]. These results indicate that the Bi-OCl-Bi12O17Cl2 composite had a matching energy band position, which was conducive to photocatalytic degradation of organic pollutants under visible-light illumination.…”
Section: Uv-vis Analysissupporting
confidence: 87%
“…Obviously, the reducibility of photogenerated e − CB on the surface of BiOI was even lower than that of SO 2− 3 (−0.94V [7]), indicating that the role of e − CB was negligible. Our previous research indicated that BiOI showed very weak adsorption of nitrate [24]. Additionally, nitrate reacts with e − aq (k(Nitrate + e − aq ) = 9.7 [26]).…”
Section: Identification Of Main Reactive Species For Mcaa Degradationmentioning
confidence: 99%
“…5g). 40–74 In addition, rGOFpl foam was used to purify the aqueous solution containing the artificial dye Rhodamine B. It was found that the UV vis characteristic peak of Rhodamine B in condensed and collected water at 570 nm disappeared after purification, and the purification efficiency was close to 100% with the color of the solution changing from pink to colorless, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%